PELATIHAN PEMBUATAN DAN PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PROMOSI USAHA MIKRO KOS–KOSAN - mamoto, Anugerah; M. Ilham Akbar HS, A.; Farsit Manoppo, Faldy; Yusupa, Ade (Education and Talent Development Center of Indonesia, 2025)
This Community Service (PkM) activity aims to increase the capacity of boarding house business owners in utilizing Instagram as an effective digital marketing medium. The activity was carried out at Kos-Kosan JR 5, Jl. Kampus Timur No. 67, Kleak, Malalayang District, Manado City, North Sulawesi. The main target is boarding house business owners who are not yet actively using social media as a means of promotion. The implementation model uses a personal approach by involving one core participant so that mentoring can be carried out intensively and in a targeted manner. The implementation method consists of four stages: (1) preparation and socialization of activities through social media, (2) counseling on the importance of social media in modern marketing, (3) technical training including the creation of business Instagram accounts and visual content, and (4) evaluation of training results through observation of account activity and its impact on business performance. The evaluation was carried out using a pre- and post-training approach to measure the increase in participant understanding, monitoring Instagram account activity for one month, and analyzing the impact on boarding house occupancy rates. The results of the activity showed that participants experienced significant improvements in digital skills, especially in managing Instagram accounts and creating content that is relevant to the target market. In addition, there was an increase in the number of uploads, account followers, and an increase in the number of new tenants in the three months after the training. This activity proves that practice-based social media training can have a real impact on the development of micro businesses. The success of this program supports the results of previous studies which state that social media can be an effective, cost-effective marketing tool and reach a wider audience in the context of MSMEs.